A Reconstructive Extensor Tendon Centralization Technique for Sagittal Band Disruption. Issue 1 (March 2020) - Vyrva, Oleksandra; Kvann, Julie; Karpinsky, Michael; Ozyurekoglu, Tuna
Abstract : Sagittal band injuries may result in extensor digitorum communis (EDC) tendon instability and may require operative treatment for symptomatic loss of extension, pain, and snapping at the metacarpophalangeal joint (MCPJ). Operative methods vary according to the source of donor tissue, as well as the anchor point of attachment. We present a surgical technique that diminishes tension of the repair with MCPJ flexion. Twenty-two EDC tendon stabilization procedures were performed between 2006 and 2017 using a tendon flap method. The selection criteria for this group of patients included completely dislocating extensor tendons with persistent complaints of pain and decrease in finger extension despite at least a 6-week conservative treatment attempt. All subjects underwent surgical treatment for tendon centralization using a distally based tendinous flap from the EDC sutured to the adjacent finger volar plate. A mathematical model was developed to analyze repair tension at 30, 60, and 90 degrees of MCPJ flexion calculating the flap length difference of 2 attachment points: deep transverse metacarpal ligament versus adjacent volar plate. Centralization was maintained in all digits with no evidence of subluxation at final postoperative evaluation. Clinical symptoms of pain and weakness resolved in all patients. Mathematical modeling provided evidence that translation of the anchor point of reconstructed flap to the volar plate of the adjacent finger resulted in lower tensile forces when compared with attachment at the intermetacarpal ligament. This optimized forces on reconstructed tendon flap experienced during MCPJ flexion. Level of Evidence: Level IV—therapeutic, case series.